TABLET ANTIMIKROBA UNTUK APLIKASI KEMASAN AKTIF - Hurun Iin; Sugiarto Sugiarto; Farah Fahma (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Antimicrobial active packaging is designed to extend the shelf life of packaged products by adding antimicrobial agents to the packaging system. Trend of green consumerism has led to an increasing demand for the use of natural antimicrobial agents for food packaging applications. The natural antimicrobial agents that are the focus of current research are essential oils, however, the application of essential oils directly to packaging materials can affect mechanical characteristics such as a decrease in the tensile strength of the packaging materials. One of the innovations to solve this weakness is the application of an antimicrobial agent with a carrier material in the form of sachets, pads and tablets. The principle of the antimicrobial active packaging is the adsorption of active compounds on the carrier material and allows the slow release of active antimicrobial compounds in the packaging system. Furthermore, challenges in the food sector related to packaging waste have prompted research on biodegradable materials, such as the use of starch and cellulose as carrier materials. This paper examines the development of antimicrobial packaging with essential oil active agents using several types of carrier materials, how to produce these packages with several types of materials, and the advantages and disadvantages of selecting the materials used.